Databases and Networks: The Benefit for Research and Quality Assurance in Patch Testing - Uter, Wolfgang; Schnuch, Axel; Giménez-Arnau, Ana M.; Orton, David; Statham, Barry (Springer International Publishing, 2020)
The systematic collection of patch test data, along with demographic and clinical information, within a (national) network has manifold advantages. As a starting point, results can be compared within the network to address possible quality problems. These could be indicated by systematically aberrant local sensitization frequencies not explained by local patient characteristics. Data of sufficient quality can be used and has been used in the past, as illustrated by several examples, for scientific analyses. Analyses may address time trends (surveillance) and subgroups or be multifactorial. Supplemental, external data sources can be linked to patch test data or used for patient management, as illustrated by some examples.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Contact dermatitis; Epidemiology; Networks; Patch testing; Quality assurance; Standardization; Surveillance